Interface characterization and thermal degradation of ferrite/poly(vinylidene fluoride) multiferroic nanocomposites - Martins, P. (2013)
Flexible multiferroic 0-3 composite films, with CoFe2O4, Ni0.5Zn0.5Fe2O4 or NiFe2O4 ferrite nanoparticles as filler and polyvinylidene fluoride (PVDF) as the polymer matrix, have been prepared by solvent casting and melt crystallization. The inclusion of ferrite nanoparticles in the polymer allows to obtain magnetoelectric (ME) nanocomposites through the nucleation of the piezoelectric -phase of the polymer by the ferrite fillers. Since the interface between PVDF and the nanoparticles has an important role in the nucleation of the polymer phase, thermogravimetric analysis (TG) was used in order to identify and quantify the interface region and to correlate it with the β-phase content. It is found an intimate relation between the size of the interface region and the piezoelectric β-phase formation that depends on the content and type of ferrite nanoparticles. The interface value and the β-phase content increase with increasing ferrite loading and they are higher for CoFe2O4 and Ni0.5Zn0.5Fe2O4 ferrite nanoparticles. The composites shows lower thermal stability than the pure polymer due to the existence of mass loss processes at lower temperature than the main degradation of the polymer. The main degradation of the polymer matrix, nevertheless, shows increased degradation temperature with increasing ferrite content.